Enhancing Micro-Pump Efficiency: Multi-Objective Optimization of Low Voltage MEMS Switches for Drug Delivery Applications - Ardehshiri, Alireza; Soltanian‬‏, ‪Farzad; Moradkhani, Masoud; Nosrati, Mehdi (Digital Technologies Research and Applications, 2024)
This paper introduces an innovative approach for designing, optimizing, and simulating a low voltage MEMS switch specialized for micro-pump applications. The primary goal is to improve the efficiency of micro-pumps used in drug delivery. The design process focuses on tailoring the switch’s geometry for micro-pump purposes and employs objective functions encompassing actuation voltage, insertion loss in the up-state, and isolation in the down-state. To solve the intricate optimization task, mathematical programming is combined with the Multi-Objective Particle Swarm Optimization (MOPSO) meta-heuristic algorithm, enabling simultaneous consideration of actuation voltage, insertion loss, and isolation. By analyzing the Pareto front derived from these parameters, the study identifies design requirements and optimal levels for the switch. The proposed MEMS switch demonstrates remarkable performance metrics, including and values of –11.74 dB and –34.62 dB at 40 GHz, a pull-in voltage of 2.8 V, and an axial residual stress of 25 MPa. This research presents an innovative strategy for optimizing capacitive switch MEMS models, using a multi-objective approach and the MOPSO algorithm to enhance efficiency in micro-pump applications.